Reliability and validation of the scale for measuring exposure to food advertising on social networks and healthy eating style of university professors - Flores-Mamani, Emilio; Neira-Ponce, Elsa-Emma; Apaza-Ticona, Jorge; Inquilla-Mamani, Juan; Apaza-Chino, Julián (International Journal of Innovative Research and Scientific Studies, 2025)
Healthy eating is important to prevent non-communicable diseases that plague modern societies. The objective of the study was to validate the reliability of the instrument for measuring the association between exposure to food advertising on social networks and the healthy eating style of university professors. The method used was quantitative, cross-sectional, and descriptive correlational, with a sample of 210 participants randomly selected from the three professional training areas of the Universidad Nacional del Altiplano - Perú, such as Social Sciences, Engineering, and Biomedical Sciences. The instrument was validated through exploratory factor analysis and Cronbach's alpha coefficient. The results show that the measurement scale is made up of three rotated factors, which explain 56.981% of the variance. The total Cronbach's alpha was 0.760, the Bartlett's test of sphericity was significant (1149.915; df = 120, sig = 0.001), and the Kaiser-Meyer-Olkin value was 0.807. It is concluded that the measurement instrument is reliable for measuring association studies of these variables, so it can explain the behavior of the phenomenon.